A descriptive and comparative analysis of injuries reported in USA Cycling-sanctioned competitive road cycling events - Gregory Jancaitis; Alison R. Snyder Valier; Curt Bay (BMC, 2022)
Abstract Background Competition in road cycling events is common, yet little is known about the nature and disposition of injuries sustained in these events. The purpose of this study is to describe injured body regions and the disposition of injuries sustained by cyclists during competitive road cycling events. Methods Data regarding body region injured and injury disposition were retrospectively analyzed from a convenience sample of 1053 injury reports (male: n = 650 [61.7%], age = 33.4 ± 13.6 years; female: n = 116 [11.0%], age = 33.3 ± 13.9 years; missing: n = 284 [27.0%]) completed during the 2016 competitive season. Results A total of 1808 injuries were reported. Injured body regions included upper extremity (46.5%, n = 841), lower extremity (32.2%, n = 583), head/neck (10.4%, n = 189), torso/back (5.2%, n = 95), face (4%, n = 87), and internal/other (0.7%, n = 13). There were 1.37 ± 0.81 injuries recorded per report. Dispositions following injury were medical attention (34.1%, n = 316), ambulance/EMS (19.3%, n = 179), report only (15% n = 139), referred (13.0% n = 121), released to parent/personal vehicle (12.1% n = 112), refused care (4.1% n = 38), and continued riding (2.5% n = 23). Males (34.0%, n = 212) received medical attention more frequently than females (23.3%), p < 0.05. Females received EMS transport (29.1%, n = 30) more frequently than males (16.8%, n = 105), p < 0.05. Conclusions Upper extremity is the most injured body region in this data set. Following injury, racers often receive medical attention and a substantial percentage require transport by EMS. Clinical relevance Anticipating the nature of injuries sustained by cyclists may promote positive health outcomes by ensuring medical teams are prepared for the immediate medical needs of cyclists.